Towards the clinical integration of an image-guided navigation system for percutaneous liver tumor ablation using freehand 2D ultrasound images. (2nd January 2015) - Spinczyk, Dominik
Abstract: Primary and metastatic liver tumors constitute a significant challenge for contemporary medicine. Several improvements are currently being developed and implemented to advance image navigation systems for percutaneous liver focal lesion ablation in clinical applications at the diagnosis, planning and intervention stages. First, the automatic generation of an anatomically accurate parametric model of the preoperative patient liver was proposed in addition to a method to visually evaluate and make manual corrections. Second, a marker was designed to facilitate rigid registration between the model of the preoperative patient liver and the patient during treatment. A specific approach was implemented and tested for rigid mapping by continuously tracking a set of uniquely identified markers and by accounting for breathing motion, facilitating the determination of the optimal breathing phase for needle insertion into the liver tissue. Third, to overcome the challenge of tracking the absolute position of the planned target point, an intra-operative ultrasound (US) system was integrated based on the Public Software Library for UltraSound and OpenIGTLink protocol, which tracks breathing motion in a 2D time sequence of US images. Additionally, to improve the visibility of liver focal lesions, an approach to determine spatio-temporal correspondence between the US sequence and the 4D computed tomography (CT) examination was developed, implemented and tested. This proposed method of processing anatomical model, rigid registration approach and the implemented US tracking and fusion method were tested in 20 anonymized CT and in 10 clinical cases, respectively. The presented methodology can be applied and used with any older 2D US systems, which are currently commonly used in clinical practice.